Shear wave estimation by using Shear Wave Holography with normal vibration: Preliminary results - Arroyo J. (2017)
Mechanical properties of soft human tissue are linked to their pathological state. One way to assess these properties is through the Young modulus measurement, which is related to the shear wave speed in the medium when considering tissues as nearly incompressible. In order to characterize its elastic properties using sonoelastography, we introduce a new technique for shear wave estimation from a static interference pattern based on Shear Wave Holography. A relation between the mathematical representation of the interference pattern and the local shear speed is derived using the Phase Derivative approach. The experimental scheme is presented, detailing the advantages of the new configuration. Homogeneous and heterogeneous elastic media were simulated, generating an interference pattern on them. The shear speed estimation algorithm was explained and applied to obtain the speed map, calculating the mean value over each medium. The technique was tested on a nearly incompressible homogeneous elastic phantom, yielding a maximum and a mean estimation error of 6% and 4.6% respectively. Overall, Shear Wave Holography using normal vibration is feasible and shows promising results in estimating shear wave speed in elastic materials. © 2017 IEEE.